Case Report: Strangulated intestinal obstruction due to chronic migration of an intrauterine device (IUD): a 30-year latent complication - Hong-Xia Song; Tian-Hao Xie; Tian-Hao Xie; Yan Fu; Xiao-Shi Jin; Qiang Wang; Zheng Niu; Qian Sun; Xiu-Hua An (Frontiers in Medicine)
Intrauterine devices (IUDs) are widely used but carry rare risks of migration and subsequent complications, such as bowel obstruction. This case highlights the life-threatening potential of chronic IUD migration decades after insertion, emphasizing the need for heightened clinical vigilance and long-term surveillance. A 57-year-old female patient presented to the hospital with a 2-day history of abdominal pain, accompanied by the cessation of flatus and defecation. She had one pregnancy and one vaginal delivery 31 years ago, followed by the insertion of a ring-shaped IUD 1 year postpartum. However, she had not undergone any follow-up examinations since the IUD placement. Two years prior to admission, she attempted to have the IUD removed, but it was not detected within the uterine cavity. This resulted in the assumption that the device had been spontaneously expelled, and no further investigations were pursued at that time. CT imaging revealed small bowel obstruction and a ring-shaped intra-abdominal foreign body. Emergency laparotomy identified a migrated IUD strangulating 100 cm of necrotic ileum. Upon exploration of the uterus, a fibroid was identified on the posterior wall, but no acute perforations or other pathological changes were noted. Subsequently, the IUD was removed, and bowel resection with anastomosis was performed. Chronic IUD migration may evade detection for decades, culminating in catastrophic bowel obstruction. Clinicians must maintain high suspicion for IUD-related complications in patients with abdominal pain, even years after insertion. Prophylactic removal of misplaced devices and long-term imaging surveillance are critical to prevent morbidity. Early recognition of such rare but severe complications through comprehensive clinical assessment and imaging studies can significantly improve patient outcomes and reduce the risk of life - threatening bowel - related events.